POKROVSK-NININSKAYA FEMALE MISSIONARY COMMUNITY: A FAILED ATTEMPT OF MISSIONARY SERVICE IN YAKUTIA - I. I. Yurganova; И. И. Юрганова (Kemerovo State University, 2016)
On the basis of historical sources, the paper considers the previously untold story of the first women's missionary community for educational purposes created in Yakutsk region in the early 20th century in the context of the all-Russian women's missionary movement. В статье рассматривается выявленная на основе исторических источников, ранее неизвестная история деятельности первой женской миссионерской общины. Она организовывалась с просветительскими целями в Якутской области в начале ХХ в. в контексте общероссийского женского миссионерского движения.